Jogo Tonggo sebagai Kebijakan Budaya: Transformasi Nilai Agama dan Tradisi Menjadi Sistem Kendali - Noorbani, Muhammad Agus; Nur, Mahmudah (Jurnal Masyarakat dan Budaya, 2023)
This article aims to explain the effectiveness of the Jogo tonggo program initiated by the Provincial Central Java Government in controlling the social and economic impacts of the Covid-19 pandemic on the people of Central Java. This research uses interviews with residents and government officials to get an idea of the effectiveness of this program. The results of this study found that Jogo tonggo goes from the caring practices carried out by the Javanese community, which comes from the combination of various religious and cultural values ​​that have been mixed up over time. It is not a form of (Javanese) cultural glorification that has been practiced for a long time but instead puts forward the aspect of how the public interest is served. Prioritizing citizen involvement in Jogo Tonggo makes this movement a form of “third way.” The third way is marked by the increasing role of the community in influencing various political policies based on the various traditional practices they have. By prioritizing the role of communities and individuals as agencies, Jogo Tonggo can overcome the far-reaching impact of the Covid-19 pandemic by reinventing and relevating the various traditions of the Javanese people.